Contemporary education: globalization and transformation process under the influence of artificial intelligence - Tsekhmister, Yaroslav; Konovalova, Tetiana; Tsekhmister, Bogdan; Pushkarova, Tamara; Nahorniak, Svitlana (Institute of Advanced Engineering and Science, 2024)
This study is aimed to investigate the problem of globalization and transformation processes in contemporary education under the influence of artificial intelligence (AI) on the basis of systemic literature review, to examine AI implications in education and to outline the opportunities for AI research in future. To achieve the objective, we analyzed 159 articles published in Scopus, Web of Science Core Collection, EBSCO, PubMed, Index Copernicus, and Google Scholar databases between 2019 and 2023. The research was conducted in accordance with the PRISMA 2020 statement in four phases: reference search, selection of relevant papers, specific analysis, evaluation of publications’ contributions and preparing the review. The results show that a great number of scientific publications are related to AI research. We found that most of the articles were published in Asia, Europe, and North America in 2022. AI tools are most used while training medical students, information technologies (IT) specialists, engineers, business or management students. The analysis of publications showed that AI is used for data analytics, introduction of personalized learning, providing feedback, online learning, and automated assessment most often. We consider that AI-driven technologies currently play an important role in education and the number of publications testify that its implementations will extend in future. The study has contributions for outlining the role of AI-related tools in educational process.